2013
DOI: 10.1002/zoos.201300010
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new leech species from North America,Helobdella austinensisn. sp. (Hirudinea: Glossiphoniidae), with observations on its feeding behaviour

Abstract: Schrägseile neigen wegen ihrer kleinen Dämpfung von 0,1%–0,15% zu windinduzierten Schwingungen. Da sich Windbedingungen ändern, sind sowohl Schwingamplitude als auch Schwingfrequenz unbekannt. Daher muss ein Seildämpfungssystem die Seile unabhängig von deren Amplitude und Frequenz gleich effizient bedämpfen. Dieser Aufsatz zeigt, wie diese Anforderung mittels echtzeitgeregelter magnetorheologischer Dämpfer erfüllt werden kann. Die Effizienz des adaptiven Seildämpfungssystems ist experimentell validiert und des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 22 publications
2
57
0
1
Order By: Relevance
“…Embryos were obtained from a laboratory colony of the species H. austinensis (Kutschera et al 2013) as described elsewhere (Gline et al 2011; Weisblat and Kuo 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Embryos were obtained from a laboratory colony of the species H. austinensis (Kutschera et al 2013) as described elsewhere (Gline et al 2011; Weisblat and Kuo 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Specimens of H. medicinalis were killed by adding 80 % ethanol to the water, so that the animals were preserved in their non-contracted, natural shape, and photographed. Extraction of DNA from part of the posterior sucker, sequencing of a fragment of the mitochondrial gene cytochrome c oxidase subunit I (CO-I), and phylogenetic analyses, based on newly acquired (and deposited) GenBank-data were performed as described (Kutschera et al , 2013Wirchansky and Shain 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Based on CO-I-sequences acquired in our laboratory for H. verbana and other leech species (Kutschera 2010(Kutschera , 2011Kutschera et al 2007Kutschera et al , 2013, supplemented by additional GenBank CO-I-data, the results shown in Table 1 were obtained. The type species H. medicinalis and its sister taxon H. verbana differ by ca.…”
Section: Phylogenetic Analysis Divergence Time and Geographic Distrimentioning
confidence: 99%
“…Only five years after its genome sequence was published (Dehal et al 2002), it was realized that the stocks labeled with this name and held in the labs in different parts of the world actually belonged to two different species, reproductively isolated but hardly distinguishable on morphological traits (iannelli et al 2007). Multiple species have also been treated as one in the case of the leech Helobdella triserialis (E. Blanchard, 1849), another popular model species (Siddall & Borda 2003;Bely & Weisblat 2006;Weisblat & Kuo 2009;Kutschera et al 2013). …”
Section: Introductionmentioning
confidence: 99%